Alcohol and Other Drug Use during Pregnancy among Women Attending Midwife Obstetric Units in the Cape Metropole, South Africa. (3rd February 2014) - Petersen Williams, Petal; Jordaan, Esmé; Mathews, Catherine; Lombard, Carl; Parry, Charles D. H.
Abstract : Little is known about the nature and extent of alcohol and other drug (AOD) use among pregnant women in Cape Town, South Africa, despite the very high levels of AOD use in this part of the country. A cross-sectional survey was conducted among pregnant women attending 11 Midwife Obstetric Units (MOUs) in greater Cape Town. A two-stage cluster survey design was used. In total, 5231 pregnant women were screened to assess self-reported prevalence estimates. Of these, 684 (13.1%) were intentionally subsampled and completed an interviewer-administered questionnaire and provided a urine sample for biological screening. Urinalyses showed that 8.8% (95% CI: 6.7–10.9) of the subsample tested positive for at least one illicit drug. This is higher than the self-reported prevalence (3.6%). In addition, 19.6% (95% CI: 16.3–22.8) of the sub-sample tested positive for alcohol which is lower than the self-reported prevalence (36.9%). There are high levels of substance use among pregnant women attending public sector antenatal clinics. There is a need for routine screening for AOD use and appropriate responses depending on the women's level of risk.